2022
DOI: 10.1289/ehp9705
|View full text |Cite
|
Sign up to set email alerts
|

A Generalizable Evaluated Approach, Applying Advanced Geospatial Statistical Methods, to Identify High Lead Exposure Locations at Census Tract Scale: Michigan Case Study

Abstract: Background: Despite great progress in reducing environmental lead (Pb) levels, many children in the United States are still being exposed. Objective: Our aim was to develop a generalizable approach for systematically identifying, verifying, and analyzing locations with high prevalence of children’s elevated blood Pb levels (EBLLs) and to assess available Pb models/indices as surrogates, using a Michigan case study. Methods: We obtained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 29 publications
1
20
0
Order By: Relevance
“…The highest amounts of Pb were found in the East North Central states and Mid-Atlantic (Figure S36), which could be associated with metal industry and power plants (31,35), but also resuspension of particles deposited in previous decades from leaded gasoline, and exterior lead paint. Recently, a study in Michigan has identified Pb hotspots at census tracts (36). We additionally found Pb hotspots across the US populated urban areas, confirming motor vehicles and traffic as a source, as also reported by the Inhalation Particle Network (31).…”
Section: Introductionsupporting
confidence: 86%
“…The highest amounts of Pb were found in the East North Central states and Mid-Atlantic (Figure S36), which could be associated with metal industry and power plants (31,35), but also resuspension of particles deposited in previous decades from leaded gasoline, and exterior lead paint. Recently, a study in Michigan has identified Pb hotspots at census tracts (36). We additionally found Pb hotspots across the US populated urban areas, confirming motor vehicles and traffic as a source, as also reported by the Inhalation Particle Network (31).…”
Section: Introductionsupporting
confidence: 86%
“…Xue et al. 15 present “a systematic approach to help identify high lead exposure locations” using state-based childhood blood lead surveillance data collected over an 11-year period (2006–2016) by the Michigan Department of Health and Human Services (MDHHS). The authors identified census tracts where children were identified with elevated BLLs (EBLLs) of , , or .…”
mentioning
confidence: 99%
“…Although there is still a lot of work to do, concerted use of evidence-based practices, primary prevention strategies, and approaches like those by Xue et al. 15 have every chance of turning the tide. We need to capitalize on the political will and current momentum at the federal, state, and local levels to finally eliminate sources of childhood lead exposure in the environment.…”
mentioning
confidence: 99%
“…32 New models using complex algorithms and mapping are useful for focusing attention on disparities in risk for exposure. 33 However, given substantial evidence of widespread exposure, targeting interventions solely to identified “hot spots” will leave many children at risk.…”
Section: Discussionmentioning
confidence: 99%
“…Another 2018 study showed that housing remains a core problem with deteriorating lead-based paint and lead dust as the main contributing environmental factor in about 90% of all childhood lead poisoning 32. New models using complex algorithms and mapping are useful for focusing attention on disparities in risk for exposure 33. However, given substantial evidence of widespread exposure, targeting interventions solely to identified “hot spots” will leave many children at risk.…”
Section: Discussionmentioning
confidence: 99%